Vitamin C as A Possible Immunity Booster - Agrawal, Anju (International Journal of Scientific Research and Management (IJSRM), 2023)
Deficiency in vitamin C, an essential micronutrient and antioxidant, may result in a compromised immune response because of its central role in immune system regulation. How effective Vitamin C might be in preventing and treating infections is an important question to answer. We reviewed the literature to learn more about vitamin C's role in the health of white blood cells (WBCs) and the expression of genes involved in the immune system and to consider whether or not vitamin C could enhance current therapies.